PENDAMPINGAN BERBASIS TEKNOLOGI ONLINE SINGLE SUBMISSION (OSS) DALAM PEMBUATAN DAN IMPLEMENTASI NIB UNTUK MENDUKUNG PENGEMBANGAN UMKM DI KELURAHAN CIGOONG - Nur Azizah, Ratu Nihayah; Manurung, Zepanya; Ayuningtyas, Vidya; Ginanjar , Gigin; Aisyah , Yurytia; Setyawati, Veratiana; Pratiwi, Desi; Puspita Hadi, Nanda; Kiptiah, Mariyatul (UNIVERSITAS SERAMBI MEKKAH, 2024)
MSME players in Cigoong Village do not fully understand the importance of NIB. This can be caused by various reasons such as lack of literacy and lack of digital skills. To increase awareness of the importance of business legality, it is necessary to support business actors in Cigoong Village to make NIB. KKM 04 created a program related to the socialization and facilitation of making NIB. With NIB, it is expected that MSME players can gain easier access to various forms of support from the government and financial institutions. The method in this research is a participatory method in which the process involves the community. And in this approach involved 2 MSMEs that did not yet have NIB. Activities were carried out on August 26 - August 30, 2024, including socialization and facilitation of making NIB in Cigoong Village. The results showed an increase in awareness of MSME actors about how meaningful NIB is and assist in making NIB through the OSS system for business development and legal protection.